Lipoprotein(a): Its Association with Calcific Aortic Valve Stenosis, the Emerging RNA-Related Treatments and the Hope for a New Era in “Treating” Aortic Valve Calcification - Donatos Tsamoulis; Iliana Siountri; Loukianos S. Rallidis (Journal of Cardiovascular Development and Disease, 2023)
The treatment of patients with aortic valve calcification (AVC) and calcific aortic valve stenosis (CAVS) remains challenging as, until today, all non-invasive interventions have proven fruitless in preventing the disease’s onset and progression. Despite the similarities in the pathogenesis of AVC and atherosclerosis, statins failed to show a favorable effect in preventing AVC progression. The recognition of lipoprotein(a) [Lp(a)] as a strong and potentially modifiable risk factor for the development and, perhaps, the progression of AVC and CAVS and the evolution of novel agents leading in a robust Lp(a) reduction, have rekindled hope for a promising future in the treatment of those patients. Lp(a) seems to promote AVC via a ‘three hit’ mechanism including lipid deposition, inflammation and autotaxin transportation. All of these lead to valve interstitial cells transition into osteoblast-like cells and, thus, to parenchymal calcification. Currently available lipid-lowering therapies have shown a neutral or mild effect on Lp(a), which was proven insufficient to contribute to clinical benefits. The short-term safety and the efficacy of the emerging agents in reducing Lp(a) have been proven; nevertheless, their effect on cardiovascular risk is currently under investigation in phase 3 clinical trials. A positive result of these trials will probably be the spark to test the hypothesis of the modification of AVC’s natural history with the novel Lp(a)-lowering agents.